Efecto de la salinidad sobre el consumo de oxígeno y la excreción de amonio de Macrobrachium rosenbergii (crustacea: Palaemonidae) - Díaz Herrera, Fernando (1993)
The metabolic rate of postlarvae and juvenile of Macrobrachium rosenbergii increased at low salinitiesbecause they required more energy to compensale for the accentuated osmotic gradient. Respiratory rate was constantat high salinities: less energy was used to hyperosmoconform. When salinity increased ammonia excretion incrementof both stages was related to the activity of the ionic Na*/NH+4 exchange bomb to balance the Na+ levels ofhemolymph. The atomic relation O:N showed that the postlarvae and juvenile prawns used carbohydrate lipid atdiluted mediums and protein at high salinities